Pengaruh Pelaksanaan Massage Terhadap Kecemasan Pada Ibu Nifas - Umi Marifah (Jurnal Keperawatan Muhammadiyah, 2019)
Objective: The postpartum period is a process of adaptation to physical and psychological changes. Anxiety is often ignored so that it goes undiagnosed. If this continues, it can cause postpartum psychological disorders. Massage intervention is one of the efforts to prevent and deal with psychological problems. This study aimed to determine the effect of giving massage with the effleurage technique on postpartum maternal anxiety.Methods: This study used a pre-experimental research design with a one-group pretest-posttest approach. The population in this study were postpartum mothers who gave birth at Al-Aqsa 4 Room, East Java Province Haji Hospital, in March 2019. The sampling technique used was simple random sampling with 22 respondents according to inclusion and exclusion criteria. The intervention was given two times for two days for 15 minutes duration. The research instrument used was the Edinburgh Postnatal Depression Scale (EPDS). The statistical test used paired t-test with a significant value of the different tests (Sig. 2-tailed)Results: The study’s results explained that the paired t-test result of 0.000 was less than 0.05. This shows a difference in the average value of anxiety before and after giving massage effleurage.Conclusion: Performing massage effleurage treatment has a significant effect on reducing postpartum maternal anxiety. Massage therapy has been proven to be effective in relieving anxiety. In addition, massage effleurage can reduce levels of hydrocortisol, adrenaline, and noradrenaline that trigger anxiety.